Comparative Mythology Synchronic and Diachronic: Structure and History for Taryo Obayashi and Claude Lévi-Strauss - Yamada, Hitoshi (2019)
Taryo Obayashi (1929-2001) was a prominent ethnologist whose wide range of interests covered kinship and family, subsistence and economy, and myth and history, among other things. Training in Frankfurt a.M. with Adolf E. Jensen, and in Vienna seeing the collapse of the so-called Culture History School, the way Obayashi studied myths appears — at least superficially — to be historically oriented. However, scrutinizing his writings carefully, it turns out that he employed structural analyses of myths more often than one would expect. In contrast, the alleged protagonist of structural mythology, Claude Lévi-Strauss (1908-2009), had a profound interest in history and diffusion especially earlier in his career. His opus magnum, Mythologiques (4 vols., 1964-71), presupposed also historically formed commonalities of American Indian mythologies as a basis for his structural exploration. In this paper, I will briefly describe Obayashi’s biography and the role he played in the academics of Japan in the 1960s-90s, a period that is less known outside the country; focus on the historical background of Lévi-Strauss’ studies of myths; shed light on the "structural-genealogical" methodologies of Obayashi, in particular in his Structure of Japanese Mythology (1975); and finally suggest that synchronic and diachronic viewpoints will enrich our understanding of myths when employed complementarily.
Keywords: Claude Lévi-Strauss; Taryo Obayashi; Mythology; Structuralism